Environmental journalism in Indonesia: in search of principles and technical guidelines - Abrar, Ana Nadhya (Penerbit Universiti Kebangsaan Malaysia, 2020)
Environmental journalism in Indonesia has a long history. An important part of this history is the presence of the “environment" rubric in Tempo news magazine. It could be treated as one of the indicators of environmental journalism development in Indonesia. However, environmental journalists in Indonesia still have fundamental weaknesses. They do not feel honored to occupy their position, do not get much access to obtain accurate information, and do not obtain many public attentions. Then, how should the practice of environmental journalism be conducted? This study has examined three environmental news in Tempo news magazine from November 2018 to February 2019. They were qualitatively analyzed through some categories, namely writing form, writing type, writing target, angle, article structure, lead, writing content, and language style. This study finds that Tempo preferred to present environmental news in the form of in-depth reporting. Tempo has implemented a series of techniques that are important for reporting environmental issues. Presumably, this can be used as a kind of technical guidelines for other print media in reporting environmental issues in Indonesia. This study also proposes some principles of environmental journalism. First, the news should comprehensively report environmental issues. Second, environmental reports should strongly have committed to biocentrism ethics and sustainable development principles. The duty of environmental journalism is to criticize the government, while its main goal is educating the public and increasing their environmental participation. In the level of news policy, it is very important to have a special desk in the environment in the newsroom.